Peran Kepala Sekolah Sebagai Adminstrator - Zaeni Dahlan; Eva Siti Faridah (AZKIA: Journal of Islamic Education in Asia, 2024)
To ensure that schools continue to exist and operate effectively, the role of the principal is crucial. Principals play a vital role as they are responsible for overseeing the progress and setbacks of the school. They must also contribute to improving the quality of education. According to Permendikbudristek Number 15 of 2018, principals are entrusted with numerous duties and responsibilities, including planning school programs, managing operations, conducting supervision and evaluations, overseeing teachers' teaching responsibilities, and managing school administration and finances. This study employs a library research or literature review method, collecting literature from various sources such as e-books, journal manuscripts, newspapers, papers, articles, reports, magazines, and relevant journals. The principal's roles can be categorized as follows: educator, manager, administrator, innovator, motivator, supervisor, and leader. The principal’s role in improving the quality of education is critical, as they significantly influence the quality of education itself. Principals are required to develop teaching program plans, student activity plans, staffing plans, financial plans, and equipment plans. Principals have two main areas of responsibility: school administration and professional development of teachers. The success of a principal largely depends on their leadership abilities.